Situación actual de los bosques de Chihuahua - Escárpita Herrera, Abraham (Instituto de Ecología, A.C., 2016)
The pine forests of the state of Chihuahua have been submitted to intensive harvesting for a number of years, without the benefit of a good management program. In the process, only the lumber has been considered important and no attention has been paid to the other services that the forest can provide. There has also been a separation between the interests of the forest owners and those of the forest products manufacturers, and no real attempts have been made to implement strategies that while permitting an increase in the forest productivity, can guarantee that the industry obtains constant supplies of quality raw materials without unduly degrading the forest resources. The forest inventories generated in the past 40 years do not reflect the exact situation of the forests neither the volumes that can be adequately extracted. The data published do not coincide with the real conditions of the forest and therefore, can not be trusted as reliable indicators to develop management programs. It is also necessary to design strategies to recover the deforested areas through the plantation of individual trees, starting from the collection and germination of seeds, while restricting the conversion of forest areas into agricultural land. Finally, it is highly desirable that programs of multiple-use of the forests be put into practice, so these can be seen not only as lumber producers with a short-time usefulness, but as providers of multiple environmental services not just for Chihuahua but for the neighboring states.